ANALYZING FACE THREATENING ACT IN WHATSAPP GROUP - Nuraeni, Wulan; Wibowo, Noer Aripin (IKIP Siliwangi, 2018)
As human being people will always interact each other every day, in every situation there are probability where someone can be threatened. Every interaction contains utterance where threatened can be happened in order to threaten both of speakers and hearer which is called Face Threatening Act or known as FTA. This research purpose was to found out the kind function of FTA in politeness that might be applied on the group chat between student with another student and student with the lecturer. The research took the places in WhatsApp group of college student of IKIP Siliwangi Bandung, Cimahi, Indonesia which consist 38 respondents. This research used a descriptive qualitative and the data taken from the results of questionnaire as an instrument. Based on the data from finding section that founded most of college students used a positive politeness when communicated with other students even though there was small percentage showed some of student used negative politeness as well.